Processing Impact on Nutritional, Antinutritional, and Phytochemical of Fenugreek Seeds (Trigonella Foenum-Graecum L.) - Adhikari, Babita; Rai, Shonu (Himalayan Journal of Science and Technology, 2021)
Phytate and tannin are more pronounced antinutrients limiting the nutritional quality of fenugreek. The impact of roasting (130±5°C for 7 minutes), soaking (12 hrs. at room temperature) and germination (72 hrs. at 25°C) on bioactive compounds (polyphenol and antioxidant activity), nutritional and anti-nutritional compounds (phytate and tannin) in Fenugreek were studied. Experimental data were analyzed using the software GenStat 12th Edition. Protein increased significantly (p<0.05) during roasting, soaking, and germination whereas fat decreased significantly. Iron and calcium increased during roasting whereas decreased during soaking and germination. Maximum reduction of phytate (54.55%) and tannin (66.73%) were found when fenugreek seeds were germinated (72 hours). The reduction percentage of antinutrients by soaking (12 hours) and roasting (130±5⁰C for 7 mins) was found to be a lesser effective method compared to germination. All the treatments had a significant (p<0.05) impact on their bioactive components. Phenolic content increased significantly (p<0.05) during roasting, soaking, and germination. Antioxidant activity (IC50=1.28mg dm/ml) was found to be high in the germinated samples as compared to raw, roasted, and soaked samples. Hence, Germination of fenugreek seeds for 72 hours is concluded as the most effective and promising method for the reduction of antinutrients and increasing the nutritional components, phytochemicals, and antioxidant properties.